(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2022)
The article presents the demographic situation of Martuni Region of the Republic of Artsakh in the post-war period. The formation of a favorable demographic situation, convenient for implementation by the regions, is of great importance for the development and implementation of state demographic policy on a scientific basis. This will ensure the normal rotation of generations, contributing to the efficient use of labor resources. The results of demographic analysis can be combined to identify and predict the main trends in the socio-economic development of both the state and its particular territorial units. In this article, we strive to find out the factors and patterns of development of demographic problems in Martuni Region of the Republic of Artsakh, the current situation, cause-and-effect relationships, to substantiate the ways to improve them. In the current situation, one of the factors determining the demography of the region is the number of refugees in the border areas, possible life risks, etc. The aggravation of many social and economic problems in the Martuni Region raises concerns, which must be resolved through economic development, increase in benefits, creation of jobs, etc. More acute is the issue of fixing settlements in the so-called demographic risk zone, the natural population growth of which is mainly due to several large families. The presence of children of different age groups supports the maintenance of the school, the club and the community center, helps to organize jobs in villages, such is in local municipalities and in medical centers. Many families have to move mainly to urban areas due to the lack of access for children to primary and secondary education, for example, in the district villages of Kavakhan, Msmna, Paravatumb, Varanda. In addition, demographic data is a sensitive system with the disadvantages of the resettlement system. In this regard, the inclusion of small settlements in the settlement system of the region is weak. The implementation of measures to increase the birth rate in a small rural settlement should become the main direction of local policy. The article discusses other issues related to the current state of the demographic movement in the current settlements of Martuni Region of the Republic of Artsakh.